A Synaptic Transistor based on Quasi‐2D Molybdenum Oxide. Issue 27 (9th May 2017) - Yang, Chuan Sen; Shang, Da Shan; Liu, Nan; Shi, Gang; Shen, Xi; Yu, Ri Cheng; Li, Yong Qing; Sun, Young
Abstract : Biological synapses store and process information simultaneously by tuning the connection between two neighboring neurons. Such functionality inspires the task of hardware implementation of neuromorphic computing systems. Ionic/electronic hybrid three‐terminal memristive devices, in which the channel conductance can be modulated according to the history of applied voltage and current, provide a more promising way of emulating synapses by a substantial reduction in complexity and energy consumption. 2D van der Waals materials with single or few layers of crystal unit cells have been a widespread innovation in three‐terminal electronic devices. However, less attention has been paid to 2D transition‐metal oxides, which have good stability and technique compatibility. Here, nanoscale three‐terminal memristive transistors based on quasi‐2D α‐phase molybdenum oxide (α‐MoO3 ) to emulate biological synapses are presented. The essential synaptic behaviors, such as excitatory postsynaptic current, depression and potentiation of synaptic weight, and paired‐pulse facilitation, as well as the transition of short‐term plasticity to long‐term potentiation, are demonstrated in the three‐terminal devices. These results provide an insight into the potential application of 2D transition‐metal oxides for synaptic devices with high scaling ability, low energy consumption, and high processing efficiency. Abstract : A quasi‐2D transition‐metal oxide, α‐phase molybdenum oxide (α‐MoO3 ), is used to fabricate nanoscale three‐terminal memristive transistors. The essential biological synaptic behaviors, such as excitatory postsynaptic current, depression and potentiation of synaptic weight, paired‐pulse facilitation, and the transition of short‐term plasticity to long‐term potentiation, are demonstrated in the three‐terminal devices.